Risk Factors for Non-optimal Resource Utilization for Emergent Interfacility Transfers by Air Ambulance in Ontario. (2nd January 2020) - Nolan, Brodie; Tien, Homer; Sawadsky, Bruce; Haas, Barbara; Saskin, Refik; Ahghari, Mahvareh; Nathens, Avery
Abstract: Background: The use of air ambulance to facilitate interfacility transfer has been associated with improved mortality; however, air ambulance is a limited resource and sometimes the optimal resource to transport a patient is unavailable. When a non-optimal resource is used there is an inherent delay and critically unwell patients may deteriorate as a result. This study aimed to identify risk factors associated with non-optimal resource utilization for adult patients undergoing emergent interfacility transport by air ambulance in Ontario, Canada. A secondary objective was to determine if non-optimal resource utilization was associated with deterioration in clinical status by measuring a delta rapid emergency medicine score (REMS). Methods : This was a retrospective cohort study of all emergent, adult interfacility transfers transported by air ambulance over a 5-year period in Ontario, Canada. Determination of optimal resource use was based on distances and historic time data for all sending-receiving facility pairs. A logistic regression model was used to explore patient, provider and institutional risk factors for non-optimal resource use. To explore the secondary objective a linear regression model was used to explore impact of non-optimal resource use on deltaREMS. Results: There were a total of 9, 687 patients included in the study cohort, with 4, 984 having an optimal resource use and 4, 703 having non-optimal resource. The median delay in interfacility transfer caused by a non-optimal transfer strategy was 35.7 minutes. Patients who required mechanical ventilation (OR 1.13, p = 0.031) and or were transferred out of nursing stations had higher odds of non-optimal resource use (OR 2.84, p = 0.019). Paramedic level of care of advanced (OR 0.37, p = < 0.001) and critical care (OR 0.28, p = < 0.001) as well as spring season (OR 0.75, p = < 0.001) had lower odds of non-optimal resource utilization. Optimal resource utilization did not significantly affect delta REMS (beta coefficient 0.002, p = 0.64). Conclusions: Patients who required mechanical ventilation and were transferred out from a nursing station had higher odds of non-optimal resource utilization while patients that required advanced or critical care level of care and spring season had lower odds of non-optimal resource use. Additionally, non-optimal resource use for air ambulance interfacility transfers did not result in patient deterioration as measured by a delta REMS score.